Corpora cavernosum abscess and corporoglanular fistula following penile shunts for ischemic priapism - Henry Wang; Ankur Dhar; Audrey Wang (Urology Case Reports, 2023)
Ischemic priapism is a urologic emergency requiring urgent intervention to prevent tissue necrosis and preserve erectile function. Cases refractory to aspiration and intra-cavernosal sympathomimetic therapy requires timely surgical shunting. Corpus cavernosum abscess following penile shunts is an exceedingly rare complication, with as few as 2 previous reported cases.We report our experience and outcome in the case of a 50-year-old patient who developed a corpora cavernosum abscess and concurrent corporoglanular fistula, following penile shunt procedures for ischemic priapism.